Mortalidade de abelhas Apis mellifera em apiários e utilização de agrotóxicos em Citrus: estudo de caso na microrregião de Araraquara (SP) - Cerqueira, Amanda (2018)
It has been increasingly constant and mediatic the mortality of bees with regard to beekeeping activity and the environmental benefits for the ecosystem balance. Several factors under the responsibility of human action are pointed out as potential precursors of mortality or weakening of colonies. Environmental contamination by the use of agrochemicals and other chemical products and the current agricultural model based on extensive monoculture areas can be mentioned as examples. From the perspective of apicultural production, the social, economic and environmental spheres are included. For the discussion of the challenges that beekeepers are currently facing in the activity, interviews were conducted with 26 beekeepers from the Araraquara microregion, in the state of São Paulo. The pesticides are considered as potentially toxic to pollinators and the orange monocultures of the region are of beekeeping interest. Thus, we sought to investigate, by field survey, the main active principles used by the citrus agro-industries of the study region. The contact was made by phone call and formalized by a Term of Responsibility. The objective was to describe the sublethal effects that these products are capable of causing Apis mellifera bees. The orange honey produced in the region was used as a matrix for laboratory analysis of residues of the active ingredients obtained by liquid and gas chromatography. It was verified that most of the pesticides under discussion belong to the chemical group of neonicotinoids and organophosphates, which are capable of causing a series of damages to the individuals and integrity of the colony. No residues of the agrochemicals obtained in the samples of orange honeys of the region were detected, but the mortality of bees in apiaries remains a frequent problem according to beekeepers interviewed.